Emotions in leader's crisis communication: Twitter sentiment analysis during COVID-19 outbreak. - Kaur, Manpreet; Verma, Rajesh; Otoo, Frank Nana Kweku (Journal of Human Behavior in the Social Environment)
Adoption of social media by political leaders for information dissemination, campaigns, and elections has been proliferating since 2008 and in 2020, 23% growth in Twitter users is observed. Past studies revealed, content and tone as the vital elements of social media communication. Therefore, current study aimed to explore on how leaders portray emotions in communication on Twitter, particularly amid crisis like COVID-19 when establishing trust is crucial for smooth dissemination of knowledge to public. Total 12128 tweets were mined from official Twitter handles of 29 Indian political leaders, from the day of COVID-19 pandemic declaration to Indian Lockdown 2.0. For analysis, NRC-based sentiment analysis of NLP is employed using R Software. Results exhibit that amongst Anger, Anticipation, Disgust, Fear, Joy, Sadness, Surprise, Trust, Negative, Positive; positive and trust are the most common emotion found whenever the authorities issued or communicated the new guidelines. Insights from results will be helpful for leaders to improve communication on virtual world considering emotions.